The roles of capitals in building capacity to address urban flooding in the shift to a new water management approach. (September 2018) - Plummer, Ryan; Renzetti, Steven; Bullock, Ryan; Melo Zurita, Maria de Lourdes; Baird, Julia; Dupont, Diane; Smith, Timothy; Thomsen, Dana
Stresses on water resources are considerable and will intensify in the future due to climatic and non-climatic drivers. The emerging shift from science-based command and control 'old' water management approach to a dynamic and integrative systems view of water—a 'new' water management approach—was explored using the concept of capacity, operationalized using the livelihoods capitals approach (i.e. physical, natural, financial, human and social capitals), as a conceptual lens in a multiple case study of notable cases of urban flooding from Canada and Australia. The findings show that there are changing conceptualizations of capacity in both cases over time. Physical and financial capitals have been emphasized for decades and are associated with the old water management approach, responding to major flood events with the construction of large control structures. While the importance of these capital inputs persists, the approach to building capacity under the emergence of the new water management approach places an increasing relative emphasis on social and human capitals. The lack of emphasis on natural capital persisted over time and should be considered explicitly in flood management. This study demonstrates how the capitals approach contributes to the very much needed understanding of how the shift from the old to a new water management approach is being expressed for both present-day decisions and long-term trajectories.